Ownership concentration and investment performance of Austrian listed companies - Nouman Afgan; Muhammad Zubair Mumtaz; Robert M. Kunst (PSL Quarterly Review)
We apply panel estimation techniques to full population of Austrian corporations from 2007-2020 in order to analyze the impact of ownership concentration on performance. Return on investment (ROI) is lower than cost of capital, which insinuates that managers invest beyond optimal investment level instead of maximizing shareholders’ wealth. ROI for pyramidal firms is 35% lower than cost of capital implying that managers pursue their objectives. State-owned firms’ ROI is 28% lower than cost of capital showing that discretionary investments lead to sub-optimal performance. An inverted U-curve is estimated with a turning point at 69% voting rights, beyond which entrenchment effect dominates the incentives effect for 37% firms. This evidence confirms minority shareholders’ expropriation, which has repercussions for efficient governance in Austrian corporations.